“Who I Am Now, Is More Me.” An Interview Study of Patients’ Reflections 10 Years After Exhaustion Disorder - Ellbin, Susanne; Jonsdottir, Ingibjörg H.; Bååthe, Fredrik (Frontiers in Psychology, 2021)
Aim: To achieve a deeper understanding of the patient’s perception regarding individual aspects related to the development of exhaustion, hindering and supporting factors in the recovery process, and potential remaining consequences, 7-12 years after receiving an exhaustion disorder diagnosis. Participants and methods: Twenty patients previously diagnosed with and treated for exhaustion disorder were interviewed 7–12 years after onset of the disease. The semi-structured interviews were transcribed verbatim and analysed with inductive content analysis. Results: Three main themes with patterns of shared meaning resulted from the analysis: “it’s about who I am”, “becoming a more authentic me”, and “the struggle never ends”. The interviewees described rehabilitation from exhaustion disorder as the start of an important personal development towards a truer and more authentic self-image. They perceived this as an ongoing long-lasting process where learned behaviour and thought patterns related to overcommitment and overcompliance needed to be re-evaluated. The results also convey long-term consequences such as cognitive difficulties and reduces energy, uncertainty about one’s own health, and the need to prioritize among one’s relationships. Conclusion: Patients with exhaustion disorder are still struggling with dysfunctional strategies and functional impairments such as cognitive problems which limit their lives, ten years after receiving their exhaustion disorder diagnosis. While informants describe some positive consequences of ED, the results also emphasize the importance of acknowledging that the patients are embedded in systems of relationships, in working life as well as in family life. This needs to be considered, together with other aspects, when working toward prevention of stress-related mental health problems.